2015
DOI: 10.1080/00221686.2015.1076532
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the flow structures of 3D turbulent offset jets

Abstract: Three-dimensional turbulent offset jets were investigated using a particle image velocimetry technique. Detailed measurements were performed for offset height ratios of 0, 2 and 4. The presence of backflow influenced the distribution of the mean velocity and Reynolds stresses. A two-point correlation analysis was used to investigate the spatial distribution of large-scale structures within the inner shear layer of the flow domain. The results revealed that large-scale structures dominate the inner layer of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…It is to be noted that complete collapse of U profiles was not attained within the backflow region. The streamwise extent for the onset of self-similarity of the 3D offset jets are less than x/b o ࣙ 38 for the no rib case reported by Nyantekyi-Kwakye et al [10]. …”
Section: Mean Velocity Profiles and Reynolds Stressesmentioning
confidence: 92%
See 3 more Smart Citations
“…It is to be noted that complete collapse of U profiles was not attained within the backflow region. The streamwise extent for the onset of self-similarity of the 3D offset jets are less than x/b o ࣙ 38 for the no rib case reported by Nyantekyi-Kwakye et al [10]. …”
Section: Mean Velocity Profiles and Reynolds Stressesmentioning
confidence: 92%
“…The objective of this study is therefore to investigate the effect of rib location on the flow structures of a 3D offset jet. The present experiment was performed at Reynolds number and flow condition similar to previous studies by Nyantekyi-Kwakye and co-workers [8,10]. Detailed velocity measurements were performed in the symmetry plane (where the interaction of the inner and outer shear layers can be modified in the presence of a surface mounted rib) using planar particle image velocimetry.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Assoudi et al [8] had investigated the mean velocity and turbulence characteristics of the turbulent offset jet using PIV technique at 3 velocity ratios and 2 offset ratios; their results indicated that increasing the offset ratio gives a better distribution of the jet within the flow field, giving rise to a better dynamic mixture. Nyantekyi-Kwakye et al [9] studied experimentally the jet with different height ratios (0, 2 and 4); their work revealed that the large scale structures within the inner layer increase with wall normal distance from the pool bottom. Further, Rathore and Das [10] reported a numerical investigation for the turbulent offset jet and compared with results proposed by Launder and Sharma [11] and Yang and Shih [12].…”
Section: Introductionmentioning
confidence: 99%